Romper os muros acadêmicos e conquistar seguidores: das narrativas públicas sobre o neomedievalismo nas mídias digitais - Motta, Gabriella Carvalho (2024)
When we consult school textbooks, watch a movie or series available on one of the streaming platforms around the world, or even look at a post on our social media, we come across different images constructed about the medieval universe. Digital media have contributed to the dissemination of these images and have allowed internet users to come into contact with different medieval forms that are not necessarily related to the historical period; this process is called neo-medievalism. Since the mid-2010s, the field of Public History here in Brazil has been interested in occupying spaces other than the academy, whether in museums, archives or even primary education, with the aim of spreading historiographical knowledge and bringing the historian community closer to society. This closeness becomes even stronger when we start experimenting with new environments, such as digital. Could Public History and Digital be allies? Our sources are immersed in this space and produce Public-Digital Histories that don't have a strict model or structure, but what connects them is the fact that they are sharing historical knowledge in digital media and weaving networks of knowledge between academic institutions, researchers, students and subjects who have no institutional ties. They also share a common theme, medievalism. The digital environment in which the sources used in this research are inserted are podcasts, hosted on Spotify, and also Instagram profiles. In the case of podcasts, we analyzed "Estudos Medievais", linked to the Laboratory of Medieval Studies at the University of São Paulo (LEME/USP), and "Medievalíssimo", produced by professor and researcher Bruno Rosa. In the case of Instagram profiles, our sources are the profiles "Barbaridades Medievais", linked to the Federal University of Triângulo Mineiro (UFTM), and "POIEMA UFpel", which disseminates content, events and other topics related to Medieval History and is organized by the Interdisciplinary Pole of Medieval and Antiquity Studies of the Federal University of Pelotas (UFPel). We also analyzed the " Memes nobres plebeus ociosos" profile. Given the extensive digital universe, we selected productions and publications shared between March/2021 and March/2022. The methodology was based on quality research, taking into account the durantion of the master's degree, and also the thematic framework, opting to select sources that discussed issues of the present time and did not abandon vocative elements of the Middle Ages. Helping to conquer a Brazilian medievalism, through the digital universe. All the sources consulted and cited during the research were cataloged using the Tropy app and are available in PDF format for our readers to consult at the end of the paper, in Appendices 2 and 3. This catalog was called "Medievalisms on the Web" and was divided according to the origin of the sources. They also have general information on the productions, such as the publications themselves, along with the title, date of publication, references, theme and other topics. Our research also used the Oral History methodology when interviewing Bruno Rosa, creator and producer of "Medievalíssimo" and José Francisco, linked to "Estudos Medievais", in order to learn more about the process of historical production in the digital universe, as well as discussing the understandings and applicability of the concept of neo-medievalism. Thus, this research contributes to the expansion of discussions on Public-Digital History, based on the analysis of Instagram profiles and podcasts that build public narratives on a new perspective of medievality that links playful and fantastical elements to present-day experiences.